Alam sebagai Terapi Kesehatan Mental - Faizal Bayu Nurfalah (UIN Sunan Gunung Djati Bandung, 2023)
This paper discusses nature as a mental health therapy, because nowadays mental health is sometimes often ignored by some people just because they are limited in their knowledge of the importance of mental health, in addition they feel that these therapies in mental illness are considered complicated. This research includes qualitative research using descriptive-analytical methods. Data sources in this study include primary and secondary sources. The primary data source of this study is the results of interviews with 3 people with categorization of people who have used nature as a medium for their mental health, such as organizations of alaman lovers, mountaineers, and others. While secondary data sources are literature related to the topic, including the literature sources are journal articles, books, and others. Data collection is carried out through indirect interviews. Meanwhile, data analysis is taken through the classification stages of several related literature. This study aims to discuss nature as a mental health therapy. This research found that there is an element of tranquility from nature itself, this is evidenced by several sources who then the resource person also felt calm when he was doing activities in the wild.